“Changing New York” The photographic cultural expression of a developing urban ideology by Berenice Abbott. - Gouliaris, Panagiotis; Giouzepas, Dimitris; Tsaras, Giannis (Urban, 2016)
Introduction The contribution of Berenice Abbott in the photographic reconstitution of the urban environment is very important and can be summarized in two main parameters. The first is the preservation of a large part of the work of Eugene Atget and its spread in America. Her sustained efforts contributed in a decisive manner to the international recognition of this great creator (Sullivan, 2006). The second parameter is her own work. Intensively influenced by the extent and the importance of Atget’s task, she traveled from Paris to New York to find a publisher for his photos. At the same time, however, she realized that this city encompassed endless possibilities of photographic exploration and decided to abandon Paris and stay there permanently. The contrasts of a changed and changing city convinced her that a comprehensive portrait of New York was very interesting. She was particularly interested in the physical changes that the city had undergone, its changing neighborhoods with huge skyscrapers replacing older low-rise buildings (Mc Caulin, 1973). She works in the traces of Atget for six years without any public support. In 1935 she is hired by Federal Art Project (FAP) as a supervisor for her “Changing New York” project which captured a modern vision of Manhattan and its surrounding boroughs in the 1930s. (Levere; Yochelson, 2005). This project is considered as one of the greatest treasures of New York’s Photographic Collection. Beginning in 1935, Abbott photographed over three hundred urban scenes which were the subject of two exhibitions at the museum, in 1937 and 1998. They remain among the most consulted and admired works in the collection, deeply evocative of their period and offering a brilliant melding of art and historical documentation. (Ibid.). One critic called her accomplishment “the finest record ever made of an American city.”(Sullivan, 2006). When Abbott took her photos, New York was emerging from possibly its most intense period of transformation. Over the course of some four decades, the skyscraper had transformed the city’s skyline and the “new” immigration had transformed the city’s culture. One of the most important things that this project reveals is that what the city is and what we see today is part of a spectrum of change and continuity that stretches back across decades and, perhaps reassuringly, reaches forward into the years yet to come (Ibid.). Keywords Cityscape; New York; photography; modern; documentary